Dynamics of Sharia Economic Fatwas: Characteristics of The Fatwa of The National Sharia Council from Classical to Contemporary - Jureid; Syukri Iska (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This research examines the transformation of the format and characteristics of Islamic economic fatwas from the classical to the contemporary model, using the fatwas of the National Sharia Council-Indonesian Ulama Council (DSN-MUI) as a case study. A qualitative method with a literature study approach and content analysis was employed. The findings reveal that DSN-MUI fatwas have undergone significant evolution, not only in substance but also in form and function. Contemporary fatwas are formulated in a more structured and formal manner, resembling regulations, and possess legal legitimacy for enforcement. The legal derivation approaches (qath'i, qauli, manhaji) integrated with the principles of al-mashlahah and maqashid al-shariah make the fatwas more responsive to the complexities of the modern economy. However, their implementation faces challenges, such as low public literacy and tensions in harmonization with the national legal system. In conclusion, this study provides recommendations for further research development, including implementation studies, compliance analysis, multidisciplinary approaches, and comparative studies with international fatwa institutions